THE EFFECT OF REWARD AND WORK SATISFACTION ON THE PERFORMANCE OF TEACHER IBNU HAJAR BOARDING SCHOOL MUNJUL CIPAYUNG EAST JAKARTA - Aswin Windia; Matin Matin; Neti Karniati (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2019)
The purpose of this study was to gain an understanding of the effect of reward on performance, the effect of job satisfaction on performance and the effect of reward on job satisfaction. This study uses a quantitative approach with survey methods and path analysis techniques. Population of 194 people, sample of 133 teachers. The sampling technique uses a simple random technique. Data collection techniques using a questionnaire. Findings, rewards have a positive effect on teacher performance. That is, the provision of better rewards will also increase the teacher's performance issued to the teacher. Job satisfaction has a positive effect on teacher performance. The better the job satisfaction received results in the increase in teacher performance. Reward has a positive direct effect on job satisfaction. providing better rewards will also increase the job satisfaction received by teachers at the educational institution Ibnu Hajar Boarding School. Key words: Satisfaction, Performance and Reward